Admission to acute mental health services after contact with crisis resolution and home treatment teams: an investigation in two large mental health-care providers. (January 2017) - Werbeloff, Nomi; Chang, Chin-Kuo; Broadbent, Matthew; Hayes, Joseph F; Stewart, Robert; Osborn, David P J
Summary: Background: Crisis resolution and home treatment teams (CRTs) offer an alternative to hospital admission for patients undergoing mental health crises in the UK. Few studies have been done to examine predictors of relapse and readmission after contact with CRTs. Methods: We used the Clinical Record Interactive Search to identify all patients receiving care from CRTs in two National Health Service (NHS) mental health trusts in London: Camden and Islington NHS Foundation Trust and South London and Maudsley NHS Foundation Trust. We used Cox regression models to examine rates and predictors of admission to acute mental health services within 1 year of contact with CRTs. Sex, age, ethnicity, marital status, social deprivation, severity of psychopathology, duration of index CRT episode, first contact with services, and diagnosis were extracted and examined as predictors of admission. Findings: Between Jan 1, 2008, and Aug 31, 2014, 17 666 patients were treated by CRTs—8759 patients in the Camden and Islington trust and 8907 patients in the South London and Maudsley trust. 53·9 patients per 100 person-years (95% CI 52·1–55·8) in Camden and Islington and 51·3 patients per 100 person-years (95% CI 49·6–53·1) in South London and Maudsley were admitted to acute services within 1 year of seeing the CRT. In both cohorts, non-affective psychotic disorders (adjusted hazard ratio [HR] 1·25, 95% CI 1·09–1·44 in Camden and Islington; 1·27, 1·17–1·38 in South London and Maudsley) and age older than 65 years (1·18, 1·01–1·37 in Camden and Islington; 1·32, 1·12–1·56 in South London and Maudsley) were associated with increased risk of admission, whereas first contact with services (0·57, 0·52–0·62 in Camden and Islington; 0·69, 0·63–0·75 in South London and Maudsley), anxiety disorders (0·81, 0·69–0·96 in Camden and Islington; 0·77, 0·67–0·87 in South London and Maudsley), and longer index CRT episodes (adjusted HR per day 0·996, 0·994–0·998 in Camden and Islington; 0·989, 0·987–0·991 in South London and Maudsley) were associated with reduced risk of admission. Interpretation: Past use of mental health services and a diagnosis of non-affective psychosis, which are markers of severity of mental illness, and older age, which is a marker of chronicity, are all risk factors for future relapse after interactions with CRTs. These findings might help clinicians and policy makers to offer more targeted and cost-effective services to reduce relapse rates. Funding: None.